ОРГАНІЗАЦІЙНО-ПЕДАГОГІЧНІ УМОВИ ВЗАЄМОДІЇ ЗДО ТА СІМ’Ї У ПІДТРИМЦІ ТА РОЗВИТКУ ТВОРЧИХ ЗДІБНОСТЕЙ ДІТЕЙ СТАРШОГО ДОШКІЛЬНОГО ВІКУ - Мороз, Інна Григорвіна (My University, 2024)
Схарактеризовано теоретичні засади проблеми розвитку творчих здібностей дітей старшого дошкільного віку. Зокрема проаналізовано творчі здібності дітей старшого дошкільного віку як психолого-педагогічна проблема. Розкрито динаміку розвитку творчих здібностей у період дошкільного дитинства. Визначено та обґрунтовано організаційно-педагогічні умови взаємодії закладу дошкільної освіти та сім’ї у розвитку творчих здібностей старших дошкільників. Здійснено експериментальне вивчення творчих здібностей дітей старшого дошкільного віку в умовах взаємодії ЗДО та сім’ї. Встановлено критерії та показники оцінки міри розвитку творчих здібностей, компоненти досліджуваного поняття. Розроблено та схарактеризовано методику констатувального етапу експерименту та визначено рівні розвитку творчих здібностей у дітей старшого дошкільного віку. Запропоновано систему роботи з підтримки та розвитку творчих здібностей дітей старшого дошкільного віку у взаємодії ЗДО та сім’ї.
The theoretical foundations of the problem of the development of creative abilities of older preschool children are characterized. In particular, the creative abilities of older preschool children were analyzed as a psychological and pedagogical problem. The dynamics of the development of creative abilities in the period of preschool childhood are revealed. The organizational and pedagogical conditions of interaction between the preschool education institution and the family in the development of creative abilities of older preschoolers have been defined and substantiated. An experimental study of the creative abilities of older preschool children was carried out under the conditions of interaction between the child care center and the family. Criteria and indicators for assessing the degree of development of creative abilities, components of the studied concept have been established. The methodology of the ascertainment stage of the experiment was developed and characterized, and the levels of development of creative abilities in older preschool children were determined. A system of work for supporting and developing the creative abilities of older preschool children in the interaction of the child care center and the family is proposed. Key words: abilities, creative abilities, development of creative abilities, organizational and pedagogical conditions, children of older preschool age, preschool education institution, family.
Keywords: здібності; творчі здібності; розвиток творчих здібностей; заклад дошкільної освіти; сім’я; організаційно-педагогічні умови; діти старшого дошкільного віку